Contemporary review of management techniques for cephalic arch stenosis in hemodialysis - Gift Echefu; Shivangi Shivangi; Ramanath Dukkipati; Jon Schellack; Damodar Kumbala (Renal Failure)
The type of hemodialysis access and its preservation impact the quality of life and survival of patients undergoing hemodialysis. Vascular access complications are among the top causes of morbidity, hospitalization, and catheter use, with significant economic burden. Poor maturation and stenosis continue to be key impediments to upper arm arteriovenous fistula feasibility. Cephalic arch is a common location for vascular access dysfunction due to its distinctive anatomy, complex valves, and biochemical alterations attributable to renal failure. Understanding cephalic arch stenosis is critical due to its high prevalence and treatment failure. The appropriate management option is highly debatable and mostly dependent on patient characteristics and interventionist’s preference. Current options include, percutaneous transluminal balloon angioplasty, stent grafts, bare metal stents, cutting balloon angioplasty, endovascular banding, and surgical procedures. This article discusses the etiologies of cephalic arch stenosis as well as currents trends in management including endovascular and surgical options.